Designing Entrepreneurial Intention with Personal Values Using Soft Systems Methodology-Based Action Research - Herliana Dewi; Rachma Fitriati; Radita Salsabila (Universitas Hayam Wuruk Perbanas, 2024)
The employment landscape in Indonesia is increasingly intricate and demands serious attention. Persistently high unemployment rates, coupled with a lower entrepreneurship ratio compared to other Southeast Asian nations, underscore the urgency for initiatives addressing entrepreneurial intention. Establishing an entrepreneurial intention program, anchored in personal values considerations, is imperative to align policies with community needs and ensure effective implementation. This study endeavors to craft entrepreneurial intentions intertwined with personal values, aimed at bolstering the entrepreneurial aspirations of both students and the broader community. The development of such a program involves a series of human activities ideally suited for analysis through soft systems methodology (SSM). Leveraging SSM, this study puts forth recommendations advocating for synergistic collaboration among the government, universities, entrepreneurs, and banking sectors. The objective is to devise a branding strategy for entrepreneurship, positioning it as an avenue for self-development and practical training enhancement through digital platforms. Effective implementation of this proposed program hinges on collaboration and synergistic communication among all stakeholders. It is essential for each entity involved to contribute collaboratively towards the seamless execution of this initiative.